Pelatihan dan Pendampingan Penyusunan Laporan Keuangan pada Usaha Tedung Mas di Desa Mekar Bhuana - Arista Pradnyani, I Gusti Agung; Ni Luh Putu Widhiastuti; Rai Dwi Andayani (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Tedung Mas is a home made Balinese umbrella business run by Mr. Agung Rai, located in Mekar Bhuana Village, Abiansemal District, Badung Regency. Tedung Mas produces home made products in the form of Balinese umbrellas which are currently being used in restaurants and hotels. The problems faced by Tedung Mas in running its business to date are the absence of recording of accounting transactions and the preparation of simple financial reports. This community service aims to provide an understanding of the importance of recording financial transactions and prohibit how to make correct financial reports so that they can then be used as material for evaluating each of their financial performance. The service is carried out through training and mentoring, as well as discussions so that the Tedung Mas business can develop better.